Analisis Peta Persebaran dan Pembandingan Hasil Forecasting Ketersediaan Beras di Kabupaten Tulang Bawang Provinsi Lampung - Br Sembiring, Noveliska -; Hapsari, Rosmawati Kunti; Marvie, Ilham (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Sumatera, 2022)
The availability of rice as a staple food commodity is one of the essential aspects in showing food security in an region, and the government must guarantee its availability. Tulang bawang regency is one of the rice barns in Lampung province, with a total population of 427,000 people. This study aims to map the condition of rice availability in Tulang bawang Regency from 2016-to 2020. In addition, this study also aims to analyze the forecasting of rice production, consumption, and availability in Tulang bawang regency. This study uses secondary data from the Food Security Office and the Statistics Center Office of Tulang bawang regency from 2016-to 2022. This research uses mapping analysis processed with microsoft excel and forecasting analysis with linear regression method. The mapping results show that the availability of rice in all sub-districts in Tulang bawang regency is moving towards a surplus from 2016-to 2020, and fewer sub-districts are experiencing a rice availability deficit. Forecasting results on production, consumption, population, and rice availability have residuals with actual data even though the movement trends are both positive.